First‐in‐human study of milvexian, an oral, direct, small molecule factor XIa inhibitor - Perera, Vidya; Wang, Zhaoqing; Luettgen, Joseph; Li, Danshi; DeSouza, Mary; Cerra, Michael; Seiffert, Dietmar (Clinical and translational science, 2022)
Milvexian (BMS‐986177/JNJ‐70033093) is a small molecule, active‐site inhibitor of factor XIa (FXIa) being developed to prevent and treat thrombotic events. The safety, tolerability, pharmacokinetics (PKs), and pharmacodynamics (PDs) of milvexian were assessed in a two‐part, double‐blind, placebo‐controlled, sequential single ascending dose (SAD) and multiple ascending dose (MAD) study in healthy adults. Participants in SAD panels (6 panels of 8 participants; n = 48) were randomized (3:1) to receive milvexian (4, 20, 60, 200, 300, or 500 mg) or placebo. The 200‐ and 500‐mg panels investigated the pharmacokinetic impact of a high‐fat meal. Participants in MAD panels (7 panels of 8 participants; n = 56) were randomized (3:1) to receive milvexian (once‐ or twice‐daily) or placebo for 14 days. All milvexian dosing regimens were safe and well‐tolerated, with only mild treatment‐emergent adverse events and no clinically significant bleeding events. In SAD panels, maximum milvexian plasma concentration occurred 3 h postdose in all fasted panels. The terminal half‐life (T1/2) ranged from 8.3 to 13.8 h. In fasted panels from 20 to 200 mg, absorption was dose‐proportional; results at higher doses (300 and 500 mg) were consistent with saturable absorption. Food increased milvexian bioavailability in a dose‐dependent fashion. In MAD panels, steady‐state milvexian plasma concentration was reached within 3 and 6 dosing days with once‐ and twice‐daily dosing, respectively. Renal excretion was less than 20% in all panels. Prolongation of activated partial thromboplastin time was observed and was directly related to drug exposure. These results suggest that the safety, tolerability, PK, and PD properties of milvexian are suitable for further clinical development.